Efektifitas Pembelajaran PAK Melalui Pondok Belajar di SMK Negeri 1 Tagulandang Utara - Deflita Lumi; Berdinata Massang (Peneliti.net, 2020)
The purpose of this study was to determine the effectiveness of PAK learning through learning cottages at SMK Negeri 1 Tagulandang Utara. This research is a qualitative research, using a descriptive approach conducted at SMK Negeri 1 Tagulandang Utara located in the Tagulandang Islands, Sitaro Regency in 2021. The data were collected through interviews, observation and documentation studies. From the results of the research data, it was found that (1) The effectiveness of PAK learning through learning cottages was still very ineffective because the learning objectives for students were not achieved as a whole, procedures or steps were not achieved, facilities were inadequate to support learning media, and the time required only 30 minutes is very less to carry out everything, (2) There are several obstacles encountered in the learning process at the learning cottage, namely the lack of interest in student learning (3) There are efforts to overcome the obstacles encountered in the learning process in the learning cottage, namely giving motivation to increase interest in learning.